Identical mitochondrial somatic mutations unique to chronic periodontitis and coronary artery disease - Tokala Pallavi; Rampalli Viswa Chandra; Aileni Amarender Reddy; Bavigadda Harish Reddy; Anumala Naveen (Wolters Kluwer Medknow Publications, 2016)
Context: The inflammatory processes involved in chronic periodontitis and coronary artery diseases (CADs) are similar and produce reactive oxygen species that may result in similar somatic mutations in mitochondrial deoxyribonucleic acid (mtDNA). Aims: The aims of the present study were to identify somatic mtDNA mutations in periodontal and cardiac tissues from subjects undergoing coronary artery bypass surgery and determine what fraction was identical and unique to these tissues. Settings and Design: The study population consisted of 30 chronic periodontitis subjects who underwent coronary artery surgery after an angiogram had indicated CAD. Materials and Methods: Gingival tissue samples were taken from the site with deepest probing depth; coronary artery tissue samples were taken during the coronary artery bypass grafting procedures, and blood samples were drawn during this surgical procedure. These samples were stored under aseptic conditions and later transported for mtDNA analysis. Statistical Analysis Used: Complete mtDNA sequences were obtained and aligned with the revised Cambridge reference sequence (NC_012920) using sequence analysis and auto assembler tools. Results: Among the complete mtDNA sequences, a total of 162 variations were spread across the whole mitochondrial genome and present only in the coronary artery and the gingival tissue samples but not in the blood samples. Among the 162 variations, 12 were novel and four of the 12 novel variations were found in mitochondrial NADH dehydrogenase subunit 5 complex I gene (33.3%). Conclusions: Analysis of mtDNA mutations indicated 162 variants unique to periodontitis and CAD. Of these, 12 were novel and may have resulted from destructive oxidative forces common to these two diseases.